2003
DOI: 10.1111/j.1572-0241.2003.07694.x
|View full text |Cite
|
Sign up to set email alerts
|

Universal precautions guideline: self-reported compliance by gastroenterologists and gastrointestinal endoscopy nurses-a decade's lack of progress

Abstract: GIEN adhered to UP recommendations better than GE regarding most items queried except in the handling of used needles. Nonetheless, for both groups, compliance with proper hand washing and use of gloves, face shields, and gowns was very poor, and handling of used needles was satisfactory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 13 publications
0
12
0
1
Order By: Relevance
“…Although drivers deal with ill people, accident victims, and sharp objects, it is observed there is a lack of knowledge regarding exposure to contagious diseases, serologic tests (12) and post-accident follow-up, since this group presented the highest level of medical assessments after accidents with sharp-edged material. Workers who reported occupational accidents are those who presented multiple lesions and those who think that cleaning the wound immediately is enough (9) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although drivers deal with ill people, accident victims, and sharp objects, it is observed there is a lack of knowledge regarding exposure to contagious diseases, serologic tests (12) and post-accident follow-up, since this group presented the highest level of medical assessments after accidents with sharp-edged material. Workers who reported occupational accidents are those who presented multiple lesions and those who think that cleaning the wound immediately is enough (9) .…”
Section: Discussionmentioning
confidence: 99%
“…Adopting precaution measures helps to control the dissemination of pathogens; the use of individual protection equipment is essential for protecting the emergency service worker in the public. Although the use of individual protection equipment does not keep the worker from having an accident, it does help to reduce the exposure to risk (12) . The investigation showed that the reality of complying with precaution measures is far from being that which is recommended (13)(14) .…”
Section: Discussionmentioning
confidence: 99%
“…Despite evidence that failure to use universal precautions increases the risk of blood-borne infections such as HIV, HBV and HCV, suboptimal adherence by health workers has been extensively reported [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…está longe de ser aquilo que é recomendada (16)(17), porém em estudo realizado nos Estados Unidos com paramédicos verificou--se que no Estado da Califórnia, onde existe legislação específica sobre manipulação de pérfuro-cortantes e que também durante a realização do estudo foram disponibilizados materiais de proteção individual em maior quantidade, os profissionais apresentaram uma maior adoção às medidas de precaução (15) . Como o conhecimento e atitude em relação a noções bá-sicas de controle de infecção e a precauções padrão foram utilizadas, neste estudo, para analisar a adoção às precauções padrão entre a equipe multiprofissional do atendimento emergencial, a categoria que demonstrou maior conhecimento teve também maior chance de adotar os princípios da biossegurança, e vice-versa.…”
Section: Resultsunclassified